Modelo estructural de las competencias profesionales del catedrático para mejorar la calidad de servicios - Limaymanta Álvarez, Cesar Halley (2014)
This study investigates the 4 dimentions o model of the university professor skills (ability, empathy, wisdom and security) adapted to the Peruvian context, particularly the city of Lima, using a second order Confirmatory Factor Analysis as a case of a model covariance structure (SEM). The model was used to test the research hypothesis of this study. The study was conducted at at the Faculty of Administrative Sciences of a public university in Lima, through a sample of 195 randomly selected participants. The results support the idea that the professor’s skills are directly related to your: competence, empathy, wisdom and safety and has the folllwing corresponding coefficients of 0.86, 0.86, 0.84 and 0.78 with significance 1 %. The model proposed in this research also meets the psychometric properties, i.e. it has an internal consistency of 0.79 and complies with the evidence of construct validity with a RMSEA index of 0.93 and GFI index of 0.054, which are the appropriate indexes. Therefore, this study provides a model for academics who are seeking to improve their performance.